Tuning intercellular adhesion with membrane-anchored oligonucleotides - Hoffecker, Ian T. (J R Soc Interface, 2019)
Adhesive interactions between cells play an integral role in development, differentiation and regeneration. Existing methods for controlling cell–cell cohesion and adhesion by manipulating protein expression are constrained by biological interdependencies, e.g. coupling of cadherins to actomyosin force-feedback mechanisms. We use oligonucleotides conjugated to PEGylated lipid anchors (ssDNAPEGDPPE) to introduce artificial cell–cell adhesion that is largely decoupled from the internal cytoskeleton. We describe cell–cell doublets with a mechanical model based on isotropic, elastic deformation of spheres to estimate the adhesion at the cell–cell interface. Physical manipulation of adhesion by modulating the PEG-lipid to ssDNAPEGDPPE ratio, and conversely treating with actin-depolymerizing cytochalasin D, resulted in decreases and increases in doublet contact area, respectively. Our data are relevant to the ongoing discussion over mechanisms of tissue surface tension and in agreement with models based on opposing cortical and cohesive forces. PEG-lipid modulation of doublet geometries resulted in a well-defined curve indicating continuity, enabling prescriptive calibration for controlling doublet geometry. Our study demonstrates tuning of basic doublet adhesion, laying the foundation for more complex multicellular adhesion control independent of protein expression.